Determination of the substrate repertoire of ADAMTS2, 3, and 14 significantly broadens their functions and identifies extracellular matrix organization and TGF‐β signaling as primary targets. Issue 5 (6th January 2016) - Bekhouche, Mourad; Leduc, Cedric; Dupont, Laura; Janssen, Lauriane; Delolme, Frederic; Goff, Sandrine Vadon‐Le; Smargiasso, Nicolas; Baiwir, Dominique; Mazzucchelli, Gabriel; Zanella‐Cleon, Isabelle; Dubail, Johanne; De Pauw, Edwin; et al.
Abstract : A disintegrin and metalloproteinase with thrombospondin type I motif (ADAMTS)2, 3, and 14 are collectively named procollagen N ‐proteinases (pNPs) because of their specific ability to cleave the aminopropeptide of fibrillar procollagens. Several reports also indicate that they could be involved in other biological processes, such as blood coagulation, development, and male fertility, but the potential substrates associated with these activities remain unknown. Using the recently described N‐terminal amine isotopic labeling of substrate approach, we analyzed the secretomes of human fibroblasts and identified 8, 17, and 22 candidate substrates for ADAMTS2, 3, and 14, respectively. Among these newly identified substrates, many are components of the extracellular matrix and/or proteins related to cell signaling such as latent TGF‐β binding protein 1, TGF‐β RIII, and dickkopf‐related protein 3. Candidate substrates for the 3 ADAMTS have been biochemically validated in different contexts, and the implication of ADAMTS2 in the control of TGF‐β activity has been further demonstrated in human fibroblasts. Finally, the cleavage site specificity was assessed showing a clear and unique preference for non‐polar or slightly hydrophobic amino acids. This work shows that the activities of the pNPs extend far beyond the classically reported processing of the aminopropeptide of fibrillar collagens and that they should now be considered as multilevel regulators of matrix deposition and remodeling.—Bekhouche, M., Leduc, C., Dupont, L., Janssen, L., Delolme, F., Vadon‐Le Goff, S., Smargiasso, N., Baiwir, D., Mazzucchelli, G., Zanella‐Cleon, I., Dubail, J., De Pauw, E., Nusgens, B., Hulmes, D. J. S., Moali, C., Colige, A. Determination of the substrate repertoire of ADAMTS2, 3, and 14 significantly broadens their functions and identifies extracellular matrix organization and TGF‐β signaling as primary targets. FASEB J. 30, 1741–1756 (2016). www.fasebj.org